2006
DOI: 10.1182/blood-2005-05-1878
|View full text |Cite
|
Sign up to set email alerts
|

Flk2+ myeloid progenitors are the main source of Langerhans cells

Abstract: Langerhans cells (LCs) are antigenpresenting cells (APCs) residing in the epidermis that play a major role in skin immunity. Our earlier studies showed that when skin is inflamed LCs are replaced by bone marrow-derived progenitor cells, while during steady-state conditions LCs are able to self-renew in the skin. Identification of the LC progenitors in bone marrow would represent a critical step toward identifying the factors that regulate LC generation as well as their trafficking to the skin. To determine LC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 40 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…Subsequent studies revealed that maintenance of DC developmental options by hematopoietic progenitors is linked to Flt3 expression and to their ability to respond to Flt3L. 43,87,88 Consistent with these data, enforced flt3 expression in early progenitor cells opens access to a DC differentiation program that can be used if no competing signals occur. 64 …”
Section: Early Hematopoietic Developmentsupporting
confidence: 48%
“…Subsequent studies revealed that maintenance of DC developmental options by hematopoietic progenitors is linked to Flt3 expression and to their ability to respond to Flt3L. 43,87,88 Consistent with these data, enforced flt3 expression in early progenitor cells opens access to a DC differentiation program that can be used if no competing signals occur. 64 …”
Section: Early Hematopoietic Developmentsupporting
confidence: 48%
“…Upon tissue damage, such as after intense UV irradiation, circulating precursors are required for replenishment. Although both myeloid and lymphoid progenitors (particularly fetal liver kinase 2 + cells) can yield LCs, CMPs are ~20-fold more efficient in this process than are CLPs (55). In vitro, circulating human CD14 + monocytes differentiate into LCs through a CD14 + CCR6 + langerin + dermal precursor (56).…”
Section: Monocyte Differentiation Into Langerhans Cells Dermal Dcs mentioning
confidence: 99%
“…Both epidermal and dermal DC are derived from flt3 receptor-positive progenitor cells and are increased in the skin following Flt3L treatments (41)(42)(43). Enhancement of Langerhans cell production by Flt3L is likely to be important in burn injury because Langerhans cells are replaced by flt3-positive bone marrow-derived progenitor cells during skin inflammation, whereas steady-state Langerhans cells are capable of self-renewal in the skin (43). Full-thickness injuries destroy the epidermal and dermal layers, so local control of wound infection is dependent upon cells migrating to the wound from other sources, possibly including the adjacent, intact skin.…”
Section: Figurementioning
confidence: 99%